2018
DOI: 10.1002/smll.201703711
|View full text |Cite
|
Sign up to set email alerts
|

Key Role of TFEB Nucleus Translocation for Silver Nanoparticle‐Induced Cytoprotective Autophagy

Abstract: Transcription factor EB (TFEB) is a master regulator of autophagy and lysosomal biogenesis. Here, silver nanoparticles (Ag NPs)-induced cytoprotective autophagy required TFEB is shown. Ag NPs-induced nucleus translocation of TFEB through a well-established mechanism involving dephosphorylation of TFEB at serine-142 and serine-211 but independent of both the mTORC1 and ERK1/2 pathways. TFEB nucleus translocation precedes autophagy induced by Ag NPs and leads to enhanced expression of autophagy-essential genes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 40 publications
3
31
2
Order By: Relevance
“…Although other NMs have been reported to target lysosomes, the detailed molecular mechanisms are still unclear. We speculated that ZNPs activated lysosomal biogenesis, which is supported by other studies . They indicated that NMs activated lysosome biogenesis due to the nucleus translocation of transcription factor EB (TFEB), which regulates the expression of genes encoding lysosomal proteins and the processing of lysosomal proteins.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Although other NMs have been reported to target lysosomes, the detailed molecular mechanisms are still unclear. We speculated that ZNPs activated lysosomal biogenesis, which is supported by other studies . They indicated that NMs activated lysosome biogenesis due to the nucleus translocation of transcription factor EB (TFEB), which regulates the expression of genes encoding lysosomal proteins and the processing of lysosomal proteins.…”
Section: Discussionsupporting
confidence: 62%
“…Nanotechnology is being a new approach to detect and intervene in certain biological processes that involve vesicular compartments, such as endosomes, lysosomes, and autophagosomes, as the major sites of nanoparticles (NPs) accumulation in cells. Several nanomaterials (NMs), such as gold, silver, and carbon‐based nanomaterials, induce autophagy as their main biological effect. Therein, autophagy is activated to eliminate foreign materials, which is important for cellular self‐protection, and recycling of the damaged proteins and organelles is promoted as well to sustain the metabolism homeostasis .…”
Section: Introductionmentioning
confidence: 99%
“…Both mTORC1 and ERK1/2 are negative regulators of TFEB and make the TFEB dephosphorylation, leading to TFEB translocates into the nucleus to execute its function, and thereby promoting autophagy and lysosome biogenesis‐related genes expression. A recent report has shown that the AgNP‐induced autophagy is mediated by TFEB, while the AgNP‐induced TFEB nucleus translation is independent of mTOR1 and ERK1/2 . In the AgNP‐treated cells, the AgNP‐induced TFEB nucleus translocation leads to the elevated level of autophagy serving as a protective mechanism in cell.…”
Section: Nm‐phagy‐related Moleculesmentioning
confidence: 98%
“…The transcription factor EB (TFEB) regulates NM‐phagy by upregulating autophagy‐related genes, and similar to LC3B, UVRAG, and p62, it can control lysosomal biogenesis . In the CeO 2 NP‐treated cells, the CeO 2 NPs help TFEB translocate from cytoplasm into nucleus and promote autophagy induction .…”
Section: Nm‐phagy‐related Moleculesmentioning
confidence: 99%
“…PVP is one of the common nanosilver coatings used in experiments to stabilize the nanosilver and prevent aggregation [42]. The effects of PVP itself has been tested at the appropriate experimental concentrations on cells and found to not cause the effects that are observed when the cells are treated with PVP-coated nanosilver [42][43][44]. Citrate is another common stabilizer, and on its own did not decrease the life span of Drosophila melanogaster [18].…”
Section: Introductionmentioning
confidence: 99%